PERENCANAAN DAN INOVASI DALAM MANAJEMEN KURIKULUM - Gustian, Indri Fitriyanti; Hanapi, Muhammad Harli; Swastini, Swastini; Manurung, Hizkia; Setiyadi, Bradley (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
The aim of this research is to study how curriculum innovation is very important to improve the quality of education and how it is relevant to the needs of society and the job market. This research method involves analyzing literature from various sources of information related to curriculum innovation. The data was analyzed descriptively to find emerging patterns and trends related to curriculum innovation. The results show that curriculum innovation, especially the Competency Based Curriculum, benefits students in improving their skills and preparing them to face future challenges. Sustainable, community-based curriculum planning is critical to discussions of these outcomes. The result is that this research emphasizes that the curriculum must be created continuously with a focus on improving students' abilities and adapting them to society's needs to provide relevant and high-quality education.